Identidades sob rasura : o documentário biográfico como reescrita gráfica e histórica da ditadura civil-militar (1964-1985) - Ronna, Giulianna Nogueira (2024)
This tesis proposes an investigation focused on the analysis of graphic writing present in contemporary Brazilian biographical documentaries that address the theme of the civil-military dictatorship (1964-1985), interrogating how the written word and trace inscribed in the image contribute to the narrative construction of historical identities. The research focuses on the benjaminian approach, in which film compositions are regarded as spaces for a critical and political rewriting of history, in dialogue with derridean philosophy, which conceives the issue of identity in its otherness, dissolution, and impossibility of apprehension. Starting from the understanding that the current political and social context of the country demands a continuous and critical review of the dictatorial period, due to the constant attacks and threats to democratic institutions, as well as the public celebration of the violence of the authoritarian regime, this thesis proposes to address the issue in the films Retratos de identificação (2014), Fico te devendo uma carta sobre o Brasil (2019), and Apiyemiyekî? (2020), as they deal with the displacements of history, its ruptures, and intervals through specific aesthetic choices, including the recurrent use of graphic elements.The adopted methodology is based on the false movements (Badiou) of cinema, through which the absorption of graphic particularities is effected. This approach, aiming to identify and compose the categories of analysis, highlights the presence of words and traces inscribed in the image, here referred to as 'graphic moments', which are observed in this study from three perspectives: plastic, historical, and identitarian, allowing access to different layers of narrative apprehension. In the compositions, the research identified the letter/writing, documents/graphemes, and self-portrait/trace as methodological markers for retaining, in their essence and depth of imagery, a correlation with the extent and experience of the subject in the world, besides being linked to the implied temporalities. By exploring the modes of inscription and how they reveal and engender new forms of apprehension of historical knowledge, what is perceived is an identity fracture, reaching only its future, bringing forth in the process an unconditional relationship with alterity, with an other, in its distances, interruptions, and invisibilities, placing the composition under erasure, under tension, being capable of modifying the viewer's historical experience and thus reaffirming cinema as a space for a critical and profound rewriting of the past.